Effects of Dhamma Practice Activities on Mindfulness and Spiritual Well-Being of Nursing Students - Sanghuaiprai, ิBenjapak; Sangpaew, Kingkaew (Saengtham College Journal, 2026)
This research employed a quasi-experimental one-group pretest-posttest design. This study aimed to investigate the Effects of Dhamma Practice Activities on Mindfulness and Well-being of Nursing Students. The sample group consisted of 80 fourth-year nursing students from St Teresa International University, academic year 2024, selected using simple random sampling. The students participated in a four-day meditation retreat. Data collection tools included the Freiburg Mindfulness Inventory (FMI-14) demonstrated a Cronbach’s alpha coefficient reliability of .96, while the Thai version of the Spiritual Well-Being Scale (Thai SWBS) demonstrated an overall reliability coefficient of .78. Data were analyzed using descriptive statistics and the paired t-test. The research findings showed that the average scores for mindfulness and well-being of nursing students after participating in meditation activities were significantly higher than before participating in the activities at the .05 statistical significance level. Furthermore, the students expressed the highest level of satisfaction with the activities. The lessons learned reflect that spiritual practice activities enhance self-awareness, emotional control, and the application of Buddhist principles in daily life. The research findings can be used as a guideline for developing appropriate activities that promote spiritual qualities and professional readiness among nursing students.